Installation and Training in Automatic Weather Station Data Tool (ADT) for the Kenya Meteorological Department - Faniriantsoa, Rija; Grossi, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The intention of this workshop was to install ADT for the Kenya Meteorological Department and provide training in its use. Installation and training took place in three sections. From February 28 – March 4 was the ADT installation, from March 7 – 11 was devoted to developing ADT components, and March 14-16 was for training in CDT.